The effect of composition of NiFe2O4 on the crystal structure of nanocomposite NiFe2O4 / PVDF that synthesized using sol gel spin coating method - Yessy Arinda Putri; - Ramli (PILLAR OF PHYSICS, 2020)
NiFe2O4 is a Ferrite Compound with the molecular formula MFe where M is a transition metal or alkaline earth is a magnetic semiconductor material with a spinel structure. The polymer used in this study is Polyvinilidene Flouride (PVDF). PVDF film is a material that is inexpensive, lightweight, flexible, has a wide frequency range, and is very sensitive. In this study 5 compositions were carried out namely ((50% : 50%), (33,3% : 66,6%), (25% : 75%), (75% : 25%), (66,6% : 33,3%)). Nanocomposites are synthesized using the sol-gel spin coating method. With making precursors (Fe(NO3) 3.9H2O and Ni(NO3) 2.6H2O. For the growth of thin films, the solution is dripped on a 0.5 cm x 0.5 cm glass substrate. Characterized using XRD (X-Rey Diffraction), SEM (Scanning Electron Microscope), FTIR (Fourier Transform Infra Red). Keywords : NiFe2O4,PVDF,Nanokompocite, Sol Gel, and Spin Coating